A preliminary study of the economic dimension of underground rock caverns for water storage in Singapore : a numerical analysis - Peh, Hoong Ping (2018)
Underground development has become an alternative way for modernised civilization to sustain the rapidly growing population especially like space-constraint country, Singapore. As Singapore lacks of sufficient water resources, national water agency known as Public Utilities Board (PUB) is discovering the feasibility to construct underground rock caverns for drainage and water storage purpose. The objective of this report is to determine the economic dimension and shape of underground rock cavern, as well as a comparison study between both poor and good rock condition has been conducted, with a focus in Bukit Timah granite rock formation in Singapore. The influence of lateral to vertical in-situ stress ratio and allowable rock pillar distance on the stability of rock cavern has been interpreted in this study. This project examines numerical analysis on the stability of unsupported rock cavern in terms of displacement, stress and plastic zone analysis. In this report, the RS2 programme that developed by the RocScience is adopted in the numerical analysis to achieve the project objectives. The entire numerical analysis started with collecting geological data properties such as uniaxial compressive strength of intact rocks, elastic modulus of the rock mass, geological strength index (GSI) and etc followed by input the required data into the RS2 programme and eventually run the computer analysis. It is found that the cavern span and height should not be too large (preferably 25m for span and 30m for cavern height) under poor rock condition. The cavern crown radius should be half of its span in order to give smaller crown displacement. Additionally, the lateral to vertical in-situ stress (k) ratio has a substantial effect on the performance of the underground rock cavern. A series of numerical investigations were performed to analyse and compare the poor and good rock conditions of Bukit Timah granite formation. The results show that good rock condition gives better overall stability performance of underground rock cavern compared to the poor rock condition. Moreover, the allowable rock pillar distance between two caverns must be kept at least 1.5 times of cavern span.